1991
DOI: 10.1073/pnas.88.3.946
|View full text |Cite
|
Sign up to set email alerts
|

Free radical-derived quinone methide mediates skin tumor promotion by butylated hydroxytoluene hydroperoxide: expanded role for electrophiles in multistage carcinogenesis.

Abstract: Free radical derivatives of peroxides, hydroperoxides, and anthrones are thought to mediate tumor promotion by these compounds. Further, the promoting activity of phorbol esters is attributed, in part, to their ability'to stimulate the cellular generation of oxygen radicals. A hydroperoxide metabolite of butylated hydroxytoluene, 2,6-di-tert-butyl4-hydroperoxyl4-methyl-2,5-cyclohexadienone (BHTOOH), has previously been shown to be a tumor promoter in mouse skin.BHTOOH is extensively metabolized by murine kerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 29 publications
2
36
0
1
Order By: Relevance
“…The data presently in hand, however, support a state of persistent oxidative stress over several weeks as the major cause of cell proliferation. Other than QMs derived from BHT or structurallysimilar alkylphenols (8,10) and an electrophilic metabolite of safrole (45), there is a paucity of specific examples of tumor promotion by electrophiles. Nevertheless, it is probable that other electrophiles of exogenous or endogenous origin influence tumor development by epigenetic mechanisms, especially if exposures occur over a prolonged period of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data presently in hand, however, support a state of persistent oxidative stress over several weeks as the major cause of cell proliferation. Other than QMs derived from BHT or structurallysimilar alkylphenols (8,10) and an electrophilic metabolite of safrole (45), there is a paucity of specific examples of tumor promotion by electrophiles. Nevertheless, it is probable that other electrophiles of exogenous or endogenous origin influence tumor development by epigenetic mechanisms, especially if exposures occur over a prolonged period of time.…”
Section: Discussionmentioning
confidence: 99%
“…In their work, the severity of BHTinduced inflammation correlated with promotion susceptibility in several inbred strains of mice. An unusual feature of this model is that the promoting agent undergoes metabolic activation in the target organ to form electrophilic metabolites that mediate its effects (7)(8)(9)(10). The para-quinone methides BHTQM and BHTOH-QM shown in Figure 1 undergo 1,6-Michael additions to thiol groups of Cys and (less rapidly) to amino groups of Lys and His residues (11,12), but specific protein targets in lungs are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the BHT quinone methide (QM) is formed from BHT-OOH and may be the ultimate tumor-promoting species derived from the latter (Guyton et al, 1991). During metabolism studies, the formation of QM along with BHT has been itself has, in spite of its high reactivity, been detected in a variety of studies.…”
Section: Introductionmentioning
confidence: 99%
“…There are two basic categories of antioxidants: synthetic and natural. The use of synthetic antioxidants is restricted because of their carcinogenicity (Kimmel and Kimmel, 1986;Guyton et al, 1991). Therefore, the development and utilization of more effective antioxidants of natural origin are desired.…”
Section: Introductionmentioning
confidence: 99%